Overview of banana and plantain (Musa spp.) improvement in Africa: past and future - Lorenzen, J.; Tenkouano, A.; Bandyopadhyay, Ranajit; Vroh, B.; Coyne, Danny L.; Tripathi, L. (International Society for Horticultural Science, 2010)
Since an unrecorded introduction from Asia in prehistoric times, banana and plantain (Musa spp.), commonly called bananas, have become major food and cash crops in Africa. The 4 million ha of bananas in Africa represent nearly a third of global production. Increased movement of plant material in the past century also introduced pests and diseases that became new constraints to banana production in Africa and have destabilized banana production with susceptible traditional landraces. Biotic challenges to banana production in the region include fungi, bacteria, viruses, nematodes and insects. Introducing host-plant resistance, whether by conventional breeding or by biotechnology, is the most economical and sustainable means of managing pests and diseases. In recent decades, progress has been made in identifying sources of host-plant resistance, identifying germplasm in other countries most like original progenitors of African landraces and developing genomic tools to increase the efficiency of developing resistant lines. Major programs for banana breeding in Africa are located in Nigeria (International Institute of Tropical Agriculture), Cameroon (Centre Africain de Recherche sur Bananiers et Plantains), and Uganda (National Agricultural Research Organization/International Institute of Tropical Agriculture). Banana breeding is slow and land intense compared to annual crops, so increasing breeding efficiency is a valuable objective. Good progress has been made in introgression resistance to black leaf streak disease, burrowing nematodes, banana weevils, and Fusarium in elite selections. There is room for progress in producing high-yielding cultivars, resistant to multiple biotic threats with similar organoleptic qualities as traditional cultivars.